The Effect of Transformational Leadership on Team Performance in The Work Environment - Purwanti, Gettik Andri; Sari, Mutia Febrina (CV. HEI PUBLISHING INDONESIA, 2024)
Transformational leadership has become one of the prominent topics in management and organizational research due to its significant impact on organizational effectiveness and team performance (Shafiyah et al., 2023). In an increasingly dynamic and complex work environment, the need for leaders who are able to inspire, motivate, and empower their teams is essential to increase productivity and innovation. This study aims at the relationship between transformational leadership style and various team performance indicators, including productivity, innovation, job satisfaction, and team commitment to the organization.This study uses a quantitative approach with an explanatory survey design to examine the relationship between transformational leadership and team performance in the workplace. The sample size is 66 employees from several departments with sample criteria, namely those who have work experience under the leadership of a transformational leader for at least one year.Based on the results in table 2, the results of the regression test (p-value 0.000) of transformational leadership on team performance show that transformational leadership has a positive and significant influence on team performance. Meanwhile, team motivation also has a positive influence on team performance (p-value 0.000) indicating that team motivation also improves performance. Transformational leadership has a significant and positive influence on team performance in the work environment. Transformational leadership encourages intrinsic team motivation through inspiration, idealized influence, and intellectual empowerment, which in turn increases team productivity and performance quality.It can be concluded that organizations must focus on developing transformational leadership and creating a work environment that supports the intrinsic motivation of team members.